Russian and Brazil media systems at the modern stage of mass communication (Proceedings of Southern Federal University. Philology, 2015)
The article describes the main characteristics of modern mass communication and media systems in Russia and Brazil. The so-called first-level media - are of elite character, aimed at the ruling classes. They are strengthening their position in the global space and almost are blurring geographical and cultural boundaries. Media audience of the second level is national, they usually focus on the middle and lower segment of the audience, if to divide it by income, education and culture. Informatization and digitalization of media lead to the formation of hybrid media systems, where there is a growing role of new media, in particular, social networks and Twitter. It is important to emphasize that the nature of the social, spiritual and cultural changes caused by informatization, depends not only on information technology, but also on the social conditions of the socioeconomic system where the implemented processes of mass communication are realized. The paper discusses the factors that determine the possibility of functioning of media systems at the present stage: the willingness of the reader to consume information and pay for it by the example of Russia and Brazil, describes the processes of globalization, information technology and digitalization of society and the media. It is presented media preferences and trust in the media in Russia and Brazil in the XXI century, as well as the main indicators of the advertising market in these countries.Keywords: Russian media system, Brazil media system, hybrid media system, twitter, culturally sensitive media.Filippova Viktoria Alexandrovna - post-graduate student of applied communications faculty of High school ofjournalism and mass communications of St. Petersburg state university. E-mail: victoria_filippova@mail.ru